Pharmacokinetic/Pharmacodynamic Target Attainment of Vancomycin, at Three Reported Infusion Modes, for Methicillin-Resistant Staphylococcus aureus (MRSA) Bloodstream Infections in Critically Ill Patients: Focus on Novel Infusion Mode - Song, Xiangqing; Han, Mi (Frontiers in Cellular and Infection Microbiology, 2022)
Objective The study aimed to evaluate and compare the pharmacokinetic/pharmacodynamic (PK/PD) exposure to vancomycin in the novel optimal two-step infusion (OTSI) vs. intermittent infusion (II) vs. continuous infusion (CI) mode, for MRSA bloodstream infections occurring in critical patients. Methods With PK/PD modeling and Monte Carlo simulations, the PK/PD exposure of 15 OTSI, 13 II, and 6 CI regimens for vancomycin, at 1, 2, 3, 4, 5, and 6 g daily dose, was evaluated. Using the Monte Carlo simulations, the vancomycin population PK parameters derived from critical patients, the PD parameter for MRSA isolates [i.e., minimum inhibitory concentration (MIC)], and the dosing parameters of these regimens were integrated into a robust mdel of vancomycin PK/PD index, defined as a ratio of the daily area under the curve (AUC0–24) to MIC (i.e., AUC0–24/MIC), to estimate the probability of target attainment (PTA) of these regimens against MRSA isolates with an MIC of 0.5, 1, 2, 4, and 8 mg/L in patients with varying renal function. The PTA at an AUC0–24/MIC ratio of >400, 400–600, and >600 was estimated. A regimen with a PTA of ≥90% at an AUC0–24/MIC ratio of 400–600, which is supposed to maximize both efficacy and safety, was considered optimal. Results At the same daily dose, almost only the OTSI regimens showed a PTA of ≥90% at an AUC0–24/MIC ratio of 400–600, and this profile seems evident especially in patients with creatinine clearance (CLcr) of ≥60 ml/min and for isolates with an MIC of ≤2 mg/L. However, for patients with CLcr of <60 ml/min and for isolates with an MIC of ≥4 mg/L, the II regimens often displayed a higher or even ≥90% PTA at an AUC0–24/MIC ratio of >400 and of >600. The CI regimens frequently afforded a reduced PTA at an AUC0–24/MIC ratio of >400 and of >600, regardless of CLcr and MIC. Conclusions The data indicated that the OTSI regimens allowed preferred PK/PD exposure in terms of both efficacy and safety, and thus should be focused more on, especially in patients with CLcr of ≥60 ml/min and for isolates with an MIC of ≤2 mg/L.